Investigation the effect of Sb on phase boundary variation of 0.965(Na0.5K0.5)(Nb1-xSbx)-0.035BaZrO3 ceramics and the corresponding piezoelectric properties. Issue 4 (2nd October 2021) - Ma, Xing-Hua; Xia, Junjia; Zhang, Zhenlu
ABSTRACT: CuO-added 0.965(Na0.5 K0.5 )(Nb1- x Sb x )-0.035BaZrO3 ceramics (0.00 ≤ x ≤ 0.10) were well prepared at 1070°C for 8 hours. And the effect of Sb 5+ ions on the phase boundary variation and the corresponding piezoelectric properties were studied. It was found that the crystal structures varied from orthorhombic-tetragonal, orthorhombic-tetragonal-rhombohedral, orthorhombic-rhombohedral PPB and finally to rhombohedral structures of 0.965(Na0.5 K0.5 )(Nb1- x Sb x )-0.035BaZrO3 with x value increasing, and the corresponding piezoelectric properties varied according to the variation of crystal structures. Particularly, the specimen with an Amm2 orthorhombic (11.1%) – R3m rhombohedral (88.9%) dominant PPB structure ( x = 0.08) showed the highest d33 value of 415 pC/N and strain of 0.12% at 4.5 kV/mm.